Reverse Debugging of Kernel Failures in Deployed Systems - Ge, Xinyang; Niu, Ben; Cui, Weidong (Proceedings of the 2020 USENIX Annual Technical Conference (ATC), 2020)
Post-mortem diagnosis of kernel failures is crucial for operating system vendors because kernel failures impact the reliability and security of the whole system. However, debugging kernel failures in deployed systems remains a challenge because developers have to speculate the conditions leading to the failure based on limited information such as memory dumps. In this paper, we present Kernel REPT, the first practical reverse debugging solution for kernel failures that is highly efficient, imposes small memory footprint and requires no extra software layer. To meet this goal, Kernel REPT employs efficient hardware tracing to record the kernel's control flow on each processor, recognizes the control flow of each software thread based on the context switch history, and recovers its data flow by emulating machine instructions and hardware events such as interrupts and exceptions. We design, implement, and deploy Kernel REPT on Microsoft Windows. We show that developers can use Kernel REPT to do interactive reverse debugging and find the root cause of real-world kernel failures. Kernel REPT also enables automatic root-cause analysis for certain kernel failures that were hard to debug even manually. Furthermore, Kernel REPT can proactively identify kernel bugs by checking the reconstructed execution history against a set of predetermined invariants.